> 其他 >
b/(a^2-ab)+c/(b^2-ab)+(a+b^2)/(a^2b-ab^2)
人气:195 ℃ 时间:2020-05-27 04:43:25
解答
b/(a^2-ab)+c/(b^2-ab)+(a+b^2)/(a^2b-ab^2)
=b/[a(a-b)]+c/[b(b-a)]+(a+b²)/[ab(a-b)]
=b/[a(a-b)]-c/[b(a-b)]+(a+b²)/[ab(a-b)]
=[ab-ac+(a+b²)]/[ab(a-b)]
=(ab-ac+a+b²)/[ab(a-b)]b/a(a-b)通分后为什么是ab/ab(a-b)这个地方看错了,谢谢你的指正!,应该是:
b/(a^2-ab)+c/(b^2-ab)+(a+b^2)/(a^2b-ab^2)
=b/[a(a-b)]+c/[b(b-a)]+(a+b²)/[ab(a-b)]
=b/[a(a-b)]-c/[b(a-b)]+(a+b²)/[ab(a-b)]
=[b²-ac+(a+b²)]/[ab(a-b)]
=(b²-ac+a+b²)/[ab(a-b)]
=(2b²-ac+a)/[ab(a-b)]
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版